Evolving therapeutics in colorectal cancer peritoneal metastases - Justin M. Bader; Nicole Aguirre; Kurt S. Schultz; Kwasi Ansere Ofori; Elizabeth Godfrey; Princy Gupta; Robert Tseng; Michael Cecchini; Raghav Sundar; Kiran Turaga (Cancer and Metastasis Reviews, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Linking conventional activated sludge treatment plant performances for micropollutants removal to environmental risk and SimpleTreat model assessment - C. Di Marcantonio; A. Chiavola; D. Spagnoli; B. Meşe; F. Margarita; V. Gioia; A. Frugis; S. Leoni; G. Cecchini; M. Spizzirri; M. R. Boni (International Journal of Environmental Science and Technology, 2024)
The attention to the contaminants of emerging concerns or micropollutants is continuously rising, also stimulated by the new initiatives at European level. The present study focuses on the removal of target micropollutants in a conventional activated sludge wastewater treatment plant which is the most common system and considered a source of micropollutants to the environment. The aims were to evaluate the removal efficiency of different stages of the wastewater treatment plant and to conduct the Environmental Risk Assessment on the final effluent. As indicated by the European’s guidelines on Environmental Risk Assessment, the SimpleTreat4.1 model was applied to this purpose: different values of the biodegradation constant, which represents the key factor for modelling, were applied, and the effects on the quality of prediction were evaluated. The evaluations were carried out thorough 3-year monitoring activity in a full-scale wastewater treatment plant on 10 micropollutants belonging to the classes of illicit drugs, pharmaceuticals and psychoactive. The model was found statistically not satisfactory for most of the investigated micropollutants. A better prediction was obtained when the biodegradation constant was calculated based on the full-scale data. Nonetheless, the results obtained in terms of risk were considered acceptable and comparable among each other. Graphical abstract

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Submarine geo-hazards on the eastern Sardinia-Corsica continental margin based on preliminary pipeline route investigation - S. Cecchini; D. Taliana; L. Giacomini; C. Herisson; B. Bonnemaire (Marine Geophysical Research, 2011)

Immunohistochemical Evaluation of Estrogen Receptor β Expression in Calf Prostates with Squamous Metaplasia - R. Stocchi; G. Renzoni; S. Rea; S. Cecchini; A. R. Loschi (Veterinary Research Communications, 2006)

Evaluation of in vitro endocytosis and antibody synthesis by rainbow trout head kidney cells treated with bovine lactoferrin - S. Cecchini; A. R. Caputo; F. Mecca (Journal of Fish Biology, 2005)
Bovine lactoferrin (LF) was evaluated for its capacity to modulate the in vitro endocytosis (phagocytosis and pinocytosis) and antibody synthesis by head kidney cells of rainbow trout Oncorhynchus mykiss . Phagocytic activity and phagocytic index of head kidney macrophages, determined by measurement of ingested yeast, were influenced by bovine LF starting from the LF concentration of 1 and 0·1 μg ml −1 , respectively. Endocytosis, determined by the evaluation of droplet uptake of neutral red dye solution, was significantly enhanced by 10 μg ml −1 of LF. In contrast, antibody synthesis by head kidney cells, evaluated by immunoenzymatic assay, from fish immunized against human‐γ‐globulins (HGG) in vivo was not affected by bovine LF. Although these results showed that bovine LF had no effect on specific immunoglobulin production in vitro , an enhancement of the acquired immune response may be assumed in LF‐treated fish in vivo , as observed in higher vertebrates.

Enhancement of pH‐resistant iron‐binding activity in supernatants of rainbow trout blood leucocytes by in vitro treatment with phorbol‐12‐myristate‐13‐acetate - S. Cecchini; A. R. Caputo; F. Mecca (Journal of Fish Biology, 2004)
Leucocyte lysates from rainbow trout Oncorhynchus mykiss showed an iron‐binding activity that was retained even if the samples were exposed to an acid pH (4·5). Iron‐binding activity of leucocyte supernatants was enhanced by the presence of 1 μg ml −1 phorbol‐12‐myristate‐13‐acetate in the cell medium.

Dehydration is more effective for the control of embryonic development and larval hatching of Diplectanum aequans (Monogenea, Diplectanidae) than formalin and trichlorphon - S. Cecchini; A.M. Cognetti-Varriale (Aquaculture International, 2003)

Influence of environmental temperature and water oxygen concentration on gas diffusion distance in sea bass (Dicentrarchus labrax, L.) - M. Saroglia; S. Cecchini; G. Terova; A. Caputo; A. De Stradis (Fish Physiology and Biochemistry, 2000)

Ascorbate dynamics in embryos and larvae of sea bass and sea bream, originating from broodstocks fed supplements of ascorbic acid - G. Terova; M. Saroglia; Z. Gy. Papp; S. Cecchini (Aquaculture International, 1998)

Variability of Surface Air Temperature in Italy 1870-1980 - T. Nanni; G. Lo Vecchio; S. Cecchini (Theoretical and Applied Climatology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)